PENERAPAN KEBIJAKAN OJK PEREKONOMIAN INDONESIA TERHADAP BANK SYARIAH MANDIRI PADA PANDEMI COVID-19 - Mega Ambarwati Sunaryo (Jurnal Ilmiah Ekonomi Bisnis, 2021)
Bank Syariah Mandiri is a form of financial institution that contributes greatly to the Indonesian economy. Coronavirus Disease-19 (COVID-19) creates similarities and comparisons in the affected economic sectors. This study aims to look at the effects of a pandemic on the Indonesian economy, the impact of the pandemic on BSM, and OKK policies during the pandemic. This research is a qualitative descriptive study. Researchers used literature review through reference books, scientific journals, online news sites, and other relevant literature. In the results of presenting the data, it is stated that the pandemic has an impact on the investment, trade, transportation and tourism sectors. The pandemic has also had a positive impact on the goals of independent Islamic bank digital transactions as an increase in the number of Mandiri Syariah Mobile customers, additional digital transactions, and additional online account creation.